Late-stage diversion risk assessment for high dams considering early initial impoundment: a case study of Lianghekou Station, China - Liu, Lian; Bricker, Jeremy D.; Hu, Chao (Frontiers in Earth Science, 2023)
Early initial impoundment can get additional generation revenue but bring more flood risk in late stage construction division. In views of the possible flood risk and catastrophic consequences caused by high dam failure induced early impoundment, a comprehensive assessment is proposed. Taking Lianghekou high rockfill dam in Yalong River the southwest China as an example, this study established the late stage diversion risk model and predicted failure probabilities for original, 15 days ahead and 30 days ahead schemes varied with initial impoundment time by Monte Carlo method. Then, considering overtopping induced gradual breaking of rock-fill dam, the NWS Dambreak flood forecasting model (DAMBRK) was used to estimate the break development and the outflow hydrograph. Due to no significant difference outflow hydrograph in three schemes, life lose was used an index for inundation consequence Combining with failure probability, life loss and early impoundment revenues brought by power generation in advance, a satisfied initial impoundment scheme was acquired by the multi-objective decision model. The results revealed this method can find a reasonable initial impoundment time in the view of the late stage diversion risk assessment.